ANALYSIS OF THIOBARBITURIC ACID AND BENZO(α) PYRENE VALUE OF SMOKED NILE TILAPIA (Oreochromis niloticus) USING DIFFERENTLIQUID SMOKES - Fronthea Swastawati; Titi Surti; Dwi Apriliani (JOURNAL OF COASTAL DEVELOPMENT, 2010)
The purpose of this research was to find the different influence of corn cob (LSA) and coconut shells (LSB) liquid smokes to the changing of thiobarbituric acid (TBA) value, benzo(α)pyrene (BP), and organoleptic value of the smoked nile tilapia during storage. The result indicated that the smoked nile tilapia which used liquid smoke corn cob had higher organoleptic value than using coconut shells. The result of organoleptic 8.60 (LSAH0), 8.24 (LSBH0), 8.02 (LSAH5), 7.88 (LSBH5), 4.91 (LSAH10), 4.56 (LSBH10) and were rejected on 10 days storage. The smoked nile Tilapia which was processed using liquid smoke of corn cob (LSA) and vacuum packed had higher organoleptic value than those which were processed by liquid smoke of coconut shells (LSB) during the storage. The different of liquid smoked gave very significant effect to TBA value (P<0.01). The duration of storage gave very significant effect to TBA value (P<0.01). The interaction between liquid smoke and duration of storage gave very significant effect (P<0.01) at 10th, 5th days, whereas at 0 day did not give very significant effect (P>0.01). TBA value of smoked nile tilapia using liquid smoke of corn cob (LSA) higher than using liquid smoke of coconut shells (LSB) for each storage (LSAH0 : 0.76; LSBH0 : 0.74; LSAH5 : 1.02; LSBH5 : 0.95; LSAH10 : 1.42; LSBH10 : 1.32). The result on polycyclic aromatic hydrocarbons (PAHs) of smoked nile tilapia using corn cob and coconut shells liquid smoke showed that there was no benzo(α)pyrene detected.